2007
DOI: 10.1021/jo0622882
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Study of 1H-Thieno[3,2-d][1,3]oxazine-2,4-dione toward the Synthesis of Bicyclic 3,4-Dihydro-1H-thieno[3,2-e][1,4]diazepine-2,5-dione Analogues

Abstract: A series of 10 optically pure 3,4-dihydro-1H-thieno[3,2-e][1,4]diazepine-2,5-dione derivatives has been synthesized in 41-75% yields on treatment of 1H-thieno[3,2-d][1,3]oxazine-2,4-dione with different natural alpha-amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…19 As expected, a slow (8-24 h) but completely selective nucleophilic attack was observed to afford the amides 7 as detected by LC-MS. Reaction time can be drastically reduced to five minutes by a preactivation of the a-aa with Et 3 N to afford at room temperature the same amides 7 with the same total selectivity (Scheme 2).…”
supporting
confidence: 72%
See 3 more Smart Citations
“…19 As expected, a slow (8-24 h) but completely selective nucleophilic attack was observed to afford the amides 7 as detected by LC-MS. Reaction time can be drastically reduced to five minutes by a preactivation of the a-aa with Et 3 N to afford at room temperature the same amides 7 with the same total selectivity (Scheme 2).…”
supporting
confidence: 72%
“…Nonetheless, this alternative solid-phase approach with a-aa (where R 3 = H) did not give higher yields and purities than our previously reported solution-phase protocol. 19 On the other hand, in accordance with our previous solution study with N-alkylated a-aa, simply heating the reaction mixtures of the solid-supported amides 12a-h (where R 3 = alkyl) at 50°C in DMF-H 2 O (4:1) for five hours directly afforded the corresponding resin-bound thienodiazepines 13a-h. These observations demonstrated that partial cis conformation induced by N-alkylation (R 3 π H) is essential for a cyclization in nonacidic conditions, in both solution-and solid-phase approaches.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…In this context, we have recently described a general synthetic protocol to generate new thieno [3,2-e] [1,4]diazepin-2,5-diones B by regioselective ring opening of 2-thiaisatoic anhydride A by α-amino acids, followed by intramolecular cyclocondensation reaction. [26] This methodology was further extended to the solid phase by using N-alkylated α-amino acids that led to C3,N4-substituted thieno [3,2-e] [1,4]diazepin-2,5-diones B (Figure 1). [27] More recently, diversity was introduced by Nsubstituted thienodiazepinedione ring opening with a series of organomagnesium bromides and subsequent cyclization to afford 5-arylthienodiazepin-2-one C analogues (Figure 1).…”
Section: Introductionmentioning
confidence: 99%